The Renin-Aldosterone Response to Stimulation and Suppression During Normal Pregnancy - Bentley-Lewis, Rhonda (Hypertens Pregnancy, 2005)
OBJECTIVE: During normal pregnancy, studies have shown increased activity of the renin-angiotensin-aldosterone system (RAAS) and a dissociation of plasma renin activity (PRA) and aldosterone (Aldo) evidenced by a greater increase in Aldo relative to PRA. The aims of this study were to examine the RAAS response to stimulation by upright posture and suppression by saline infusion and to investigate the PRA-Aldo dissociation under these two conditions. METHODS: We studied 24 healthy normotensive women (mean ± standard error of mean, ages 29 ± 1 yrs) in sodium (Na) balance in the second and third trimesters and postpartum. Subjects underwent a 24-hour urine collection which was analyzed for Na, norepinephrine (NE), epinephrine (Epi), and dopamine (DA); a posture study with analysis of blood pressure (BP), PRA, Aldo, NE, Epi, DA, and cortisol; and a 0.9% NaCl infusion study (500 mL/hr for 3 hrs) with analysis of BP, PRA, Aldo, cortisol, and digitalis-like factor (DLF). Analyses included paired t tests to compare posture and saline responses, repeated measures to compare across periods, and percent change to evaluate the PRA-Aldo dissociation. RESULTS: During pregnancy, PRA, Aldo, BP, catecholamines, and cortisol levels were significantly greater in upright than left lateral decubitus (LLD) posture, and the percent change in Aldo was significantly greater than the percent change in PRA. During pregnancy in response to saline infusion, BP did not change; the PRA and Aldo significantly decreased; the percent change in Aldo was significantly greater than the percent change in PRA in the second trimester; and serum DLF and cortisol levels significantly decreased. CONCLUSIONS: In longitudinally studied normal pregnancy, PRA and Aldo levels were dissociated at baseline, with stimulation and, to a lesser degree, with suppression. Norepinephrine, adrenocorticotrophic hormone, and DLF may contribute to this dissociation, and clarification of these interactions may provide insight into the regulation of aldosterone during normal and hypertensive pregnancy.